Romanian Community in Austria Social and economic Integration - Marian-Ionel CUTOI (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene, 2020)
Migration is a social phenomenon that has profoundly affected Romanian society for the last three decades. Due to migration, in some receiving states, more representative communities of Romanians began to develop. One of these communities is that of the Romanians in Austria, which in recent years has developed steadily, becoming the second-largest minority community in this country. The influencing factors and the contextual environment influenced both the immigration and the socio-economic integration of the Romanians into the Austrian society. Evidence of this integration is given by a high rate of engagement in the labour market, entrepreneurship and the school system. Romanians are not only a well-integrated community, but also human capital that plays a particularly important role in certain areas of socio-economic life in Austria.